Penyusunan Peta Administrasi Desa Tanjung Kuaw Kabupaten Seluma Menggunakan Aplikasi GIS - Al Ikhsan Rama Komura; Dedi Guntar; Mirna Yunita; Al Furkon Sabda Aradepa; Muhammad Alfi (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2023)
Compilation of Administrative Maps Using ArcGIS 10.3 Application The purpose of this research is to Manage/Record the coordinate points of boundaries, facilities, and village potential. The Tanjung Kuaw Village map has not been updated properly to find out the village boundaries, facilities, and village potential. Village boundaries aim to determine an administrative boundary between villages which is a coordinate point on the earth's surface in the form of natural signs and man-made elements that are outlined in the form of a map. The preparation of this administrative map starts from the basic data of the Village Map (SHP form), followed byaerial photographs obtained through the Unmanned Aerial Vehicle (UAV) to obtain data on Tanjang Kuaw Village covering an area of 959.39 Hectares, then visual interpretation and manual detection of aerial photography data of Tanjung Kuaw village is carried out to obtain information on village facilities and potential (Interpretation is carried out using ArcGIS 10.3 application with a scale of 1: 5,000).